Associations of serum and tissue TIMP1 with host response and survival in colorectal cancer - Akseli Kehusmaa; Anne Tuomisto; Päivi Sirniö; Henna Karjalainen; Meeri Kastinen; Vilja V. Tapiainen; Ville K. Äijälä; Taina Tervahartiala; Timo Sorsa; Jukka Rintala; Sanna Meriläinen; Juha Saarnio; et al. (Scientific Reports)
Abstract Tissue inhibitor of matrix metalloproteinase 1 (TIMP1) is a multifaceted, cytokine-like bioactive molecule whose levels are elevated in a wide range of inflammatory diseases and are associated with prognosis. Additionally, TIMP1 may play a role in driving systemic inflammation. TIMP1 immunohistochemistry and TIMP1 serum concentrations were analyzed in a cohort of 776 colorectal cancer patients. TIMP1 histoscore by cell type (tumor cell, other) was quantified using digital image analysis. Serum TIMP1 levels were evaluated for correlations with tumor TIMP1 expression, and their associations with tumor characteristics, inflammation, and prognosis were investigated. High serum TIMP1 concentrations associated with shorter overall survival (multivariable HR 1.85, 95% CI 1.30–2.65). Serum TIMP1 levels positively correlated with markers of systemic inflammation and tumor necrosis percentage but not with TIMP1 expression in tumor tissue. High TIMP1 intensity in tumor stroma associated with longer cancer-specific and overall survival in univariable analysis but not in multivariable models. T cell densities in tumor tissue positively correlated with tumor stromal TIMP1 expression and negatively with tumor epithelial TIMP1 expression. Serum TIMP1 levels show promise as a prognostic marker for colorectal cancer and correlate with systemic inflammatory markers, but do not correlate with TIMP1 expression in tumor tissue.